Ethical evaluation of GMO from an Islamic perspective - Mahmod, Safa Senan; Kabbashi, Nassereldeen Ahmed (2013)
In recent years, genetic engineering has been used to modify and improve plants, animals and microorganisms to improve their value to fulfill human needs. Genetic engineering technology’s focuses are into three major uses: medication, food and agriculture. GMO technology with both of its positive and negative impacts is strongly discussed by many consumers, environmental groups and scientists. As the impact of this powerful technology cannot be predicted, the safety of modern biotechnology products need to be analyzed in a careful scientific procedure and has to be controlled with Islamic ethics to ensure that this technology can guide us towards happiness with a healthier life and environment. Islamic ethics of modern biotechnology, especially GMO technologies, are categorized according to three part of akhlaq: ethical issues related to God (Allah), ethics related to the safety of all the creations and ethics related to the environment. In this paper, ethical aspects of modern biotechnology will be discussed from an Islamic perspective to be followed by the Khalifah on earth, accompanied with real-life examples of the benefits and risks, and Islam’s opinion on this issue inspired by verses from Al-Quran and Hadith quotations.